Fabrication and characterization of a novel bionic manipulator using a laser processed NiTi shape memory alloy. (February 2020) - Zeng, Zhi; Oliveira, J.P.; Ao, Sansan; Zhang, Wei; Cui, Jiangmei; Yan, Shuo; Peng, Bei
Highlights: A bionic manipulator was fabricated by laser processing of a NiTi alloy. The phase transformation behaviour depend on the laser processing parameters. The electrical-thermo-mechanical behavior is based on alloy shape memory effect. The bionic manipulator can be helpful for patients with hand paralysis. Abstract: The thermo-mechanical properties of NiTi shape memory alloys (SMAs) have sparked significant research efforts seeking to exploit their bionic capabilities. Currently, the performance capabilities of NiTi-based devices have been inhibited by the retention of only one thermo-mechanical response in the as-received material, namely the shape memory effect (SME) or superelasticity (SE), which mainly depend on the transformation temperatures of the base material. In this work, a novel monolithic bionic manipulator was developed using a NiTi SMA by laser processing, which included both the shape memory and superelastic effects in a single Ni-rich monolithic structure. The device actuation and bending were achieved by resistive heating, which activates the SME of different laser processed regions. Each laser processed region has unique phase transformation onset temperatures and thermo-mechanical recovery characteristics thus providing distinct actuation characteristics. Additionally, the functional fatigue of the part was determined for rehabilitation training of patients including the fingers pairing and grabbing modes.